FORMS OF LEGAL PROTECTION DUE TO THE CONVERSION OF AGRICULTURAL LAND INTO RESIDENTIAL AND INDUSTRIAL LAND - Saiful Munir; Siti Afiyah; Ahmad Munir (SYNTIFIC, 2023)
Background. Indonesia is a developing country that cannot be separated from modernization. Thus, if Indonesia turns into a modern country, it must change itself from an agrarian country to an industrial country. Local government and related agency officials in an effort to realize the protection of sustainable food land are still limited to carrying out their main duties and functions as outlined in the local regulation, there are no other sociological efforts aimed at realizing the protection of sustainable agricultural land. The purpose of this research was 1) to find out the government's legal products in reducing the conversion of agricultural land into housing and industrial land, 2) to find out the form of legal protection due to the conversion of agricultural land into Housing and Industrial land. Research Method. This research used normative juridical that examine the regulations both legislation and other regulations under the law that have a relationship with research problems. In conducting research, the author uses several approaches, including a statutory approach, conceptual approach, historical approach and comparative approach. Findings. The conversion of agricultural land to non-agricultural uses in various regions in Indonesia is mostly carried out by the landowners themselves and is influenced by other factors both internal and external as well as policy factors from the government. Conclusion. The conversion of land that has been designated as sustainable food agricultural land for the public interest can only be carried out on the condition that a strategic feasibility study.